1976
DOI: 10.1111/j.1751-1097.1976.tb06778.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Disulfide Groups With Nucleic Acid Bases

Abstract: Abstract— Low temperature luminescence studies have provided evidence for interactions between the disulfide group of cystamine and adenine bases in cystamine‐poly(A) complexes and in cystamine‐adenosine aggregates. A quenching of adenine phosphorescence by cystamine was observed. At room temperature complex formation between cystamine and poly(A) was followed by proton magnetic resonance, absorption spectrophotometry and fluorescence using competition with a fluorescent peptide to monitor the binding process.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1977
1977
1982
1982

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…results seem to exclude stacking interaction in headpiece-lac operator complexes (Nick et al, 1982). For energy transfer from tyrosine to the nucleic acid bases the critical Forster distance can be as high as 20 A (Montenay-Garestier, 1975). Therefore, tyrosine fluorescence can be quenched even if the residue is not engaged in any close contact interaction (such as hydrogen bonding) with the DNA.…”
Section: Discussionmentioning
confidence: 99%
“…results seem to exclude stacking interaction in headpiece-lac operator complexes (Nick et al, 1982). For energy transfer from tyrosine to the nucleic acid bases the critical Forster distance can be as high as 20 A (Montenay-Garestier, 1975). Therefore, tyrosine fluorescence can be quenched even if the residue is not engaged in any close contact interaction (such as hydrogen bonding) with the DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Shafferman and Stein (1974) have shown that the reaction of dithioglycolic acid, an analog of cystine, to form thioglycolic acid can be photosensitized by tyrosine at acid pH through electronic energy transfer. Montenay-Garestier et al (1976) have shown that excited poly A interacts with cystamine, possibly leading to S-S bond rupture. It is possible that energy transfer or other interactions of photoexcited bases with cystine could lead to the formation of cysteine.…”
Section: Photoreactions Of Nucleic Acids and Their Constituents With mentioning
confidence: 98%
“…Energy transfer from tyrosine to nucleic acid bases appears as the most likely explanation for quenching. The calculated Forster distances for singlet energy transfer gave values ranging from 10 to 17A depending on the nature of the base (Montenay-Garestier, 1975). As methylation of the hydroxyl group does not change greatly either the overlap integrals or Forster critical distances energy transfer can explain the results obtained with peptides containing either methylated or unmethylated tyrosine residues.…”
Section: Resultsmentioning
confidence: 86%
“…Several mechanisms could explain such a quenching : (i) stacking between nucleic bases and phenol rings. This interaction was demonstrated in single stranded polynucleotide-oligopeptide complexes (Dimicoli and Helene, 1972); (ii) energy transfer from tyrosine to nucleic acid bases (Montenay-Garestier, 1975); (iii) hydrogen bonding between the hydroxyl group of tyrosine and acceptor sites of nucleic acids (Sellini et a!., 1973;Lancelot, 1977) followed by proton transfer in the excited state; (iv) a protein conformational change which brings an inhibitor group of the peptidic chain in the vicinity of the tyrosyl residues.…”
Section: Introductionmentioning
confidence: 96%